ADAPTASI DAN MITIGASI PEMANASAN GLOBAL - Rachmad Wide; Muhammad Hakim; Eri Barlian (Jurnal Kependudukan dan Pembangunan Lingkungan, 2020)
The causes of global warming are directly related to the greenhouse effect. If the amount of greenhouse gases increases in the atmosphere, the effect of global warming will be even more significant. Since the industrial revolution, greenhouse gases such as carbon dioxide, methane, and other harmful gases have increased in the atmosphere so that their concentration has increased due to human activity. Global warming is thought to have caused system changes to ecosystems on earth, among others; extreme climate change, melting ice so that sea levels rise, and changes in the amount and pattern of precipitation. The existence of system changes in this ecosystem has had an impact on life on earth such as affecting agricultural products, the loss of glaciers and the extinction of various types of animals. In the form of traditional culture, local wisdom gives birth to ethics and norms of community life in utilizing natural resources and the environment. As long as the community still respects traditional cultures that have ethical and moral values towards their natural environment, conservation of natural resources and the environment is an absolute must.